Is There a Place for Family-centered Cesarean Delivery during Placenta Accreta Spectrum Treatment? - Albaro José Nieto-Calvache; Alejandra Hidalgo; Juliana Maya; Beatriz Sánchez; Luisa Fernanda Blanco; Stiven Ernesto Sinisterra-Díaz; Juan Pablo Benavides-Calvache; Iván Padilla; Ivonne Aldana; Martha Jaramillo; Ana Maria Gómez; Angela María Olarte Castillo; et al. (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2023)
ABSTRACT Objective Placenta accreta spectrum (PAS) is a cause of massive obstetric hemorrhage and maternal mortality. The application of family-centered delivery techniques (FCDTs) during surgery to treat this disease is infrequent. We evaluate the implementation of FCDTs during PAS surgeries. Methods This was a prospective, descriptive study that included PAS patients undergoing surgical management over a 12-month period. The patients were divided according to whether FCDTs were applied (group 1) or not (group 2), and the clinical outcomes were measured. In addition, hospital anesthesiologists were surveyed to evaluate their opinions regarding the implementation of FCDTs during the surgical management of PAS. Results Thirteen patients with PAS were included. The implementation of FCDTs during birth was possible in 53.8% of the patients. The presence of a companion during surgery and skin-to-skin contact did not hinder interdisciplinary management in any case. Conclusion Implementation of FCDTs during PAS care is possible in selected patients at centers with experience in managing this disease.